2015
DOI: 10.1186/s12903-015-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior maxilla alveolar ridge dimension and morphology measurement by cone beam computerized tomography (CBCT) for immediate implant treatment planning

Abstract: BackgroundImplants have been widely used to restore missing teeth. Limited information on applied anatomy at the anterior maxilla compromises the clinical outcome for implant placement in this region. In the current study, Cone Beam Computerized Tomography (CBCT) was used to measure alveolar ridge and buccal undercut dimension at the anterior maxilla to help develop treatment planning for immediate implant placement.MethodsCBCT scans were screened to include 51 subjects with full dentition at right maxilla. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
3
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 29 publications
10
88
3
11
Order By: Relevance
“…Conversely, these results disagree with a study (Zhang et al, 2015)which found that males demonstrated significantly larger alveolar width compared to females for anterior maxilla.…”
Section: Discussion:-contrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, these results disagree with a study (Zhang et al, 2015)which found that males demonstrated significantly larger alveolar width compared to females for anterior maxilla.…”
Section: Discussion:-contrasting
confidence: 99%
“…This method for selecting the desired cross-sectional image was innovated by the researchers who performed this work. Alveolar Ridge Height:-On the selected cross-sectional cut, a line was plotted and measured perpendicular to another two lines drawn parallel and tangential to the alveolar crest and the nearest anatomical landmark (e.g., floor of the nasal cavity orthe maxillary sinus) (Zhang et al, 2015;Zheng et al, 2015) (Fig 7).…”
Section: Cbct Imaging Acquisition:-mentioning
confidence: 99%
See 1 more Smart Citation
“…If the implant had not been inserted in a one‐stage procedure and ridge augmentation had been performed previously, the most recent CBCT before ridge augmentation was used. The alveolar ridge width was measured using a protocol of Zhang et al . An example of the measurement method is shown in the figure below (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Se ha descrito la normalidad y variaciones anatómi-cas para ambos huesos en distintas poblaciones (Cova et al 2003;Jacobs et al 2002;Katakami et al 2009;Kawashima et al 2015; Patil et al 2012;Zhang et al 2015). Este artículo se enfoca en la presencia y características del foramen lingual ubicado en la línea mediana, descrito en la tabla lingual del sector mandibular anterior.…”
Section: Introductionunclassified